The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1039/d3md00511a
|View full text |Cite
|
Sign up to set email alerts
|

Latest developments in coumarin-based anticancer agents: mechanism of action and structure–activity relationship studies

Manankar Koley,
Jianlin Han,
Vadim A. Soloshonok
et al.

Abstract: Many researchers all around the world are working on the development of novel anticancer drugs with different mechanisms of action. Coumarin is a highly promising pharmacophore for the development of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 247 publications
1
5
0
Order By: Relevance
“…These results could be explained by the fact that both, coumarin and chalcone, involve many anticancer mechanisms, including cell cycle arrest, ROS production and apoptosis. [31,[58][59][60] This is also in accordance with those previous reports made by Wang and colleagues [46] who showed a coumarin-chalcone hybrid which efficiently delivered to cells to induce apoptosis through the generation of intracellular ROS in a colorectal carcinoma cell line HCT116. Besides, in other study, Singh and colleagues [61] had demonstrated that a coumarin-chalcone hybrid caused cell cycle arrest at G2/M phase and induced intrinsic caspase-dependent apoptosis mediated by alterations in the cellular levels of Bcl-2 family proteins in cervical cancer cell lines (HeLa and C33A).…”
Section: Antiproliferative Effect Of Hybrid 3c On Human Colorectal Ad...supporting
confidence: 91%
See 2 more Smart Citations
“…These results could be explained by the fact that both, coumarin and chalcone, involve many anticancer mechanisms, including cell cycle arrest, ROS production and apoptosis. [31,[58][59][60] This is also in accordance with those previous reports made by Wang and colleagues [46] who showed a coumarin-chalcone hybrid which efficiently delivered to cells to induce apoptosis through the generation of intracellular ROS in a colorectal carcinoma cell line HCT116. Besides, in other study, Singh and colleagues [61] had demonstrated that a coumarin-chalcone hybrid caused cell cycle arrest at G2/M phase and induced intrinsic caspase-dependent apoptosis mediated by alterations in the cellular levels of Bcl-2 family proteins in cervical cancer cell lines (HeLa and C33A).…”
Section: Antiproliferative Effect Of Hybrid 3c On Human Colorectal Ad...supporting
confidence: 91%
“…A structure-activity relationship (SAR) was rationalized by analyzing the substituents effects and it revealed key differences between those evaluated hybrids 3 a-h (Figure 3 Thereon, different studies have been reported with coumarin and chalcone derivatives, showing the great potential of these two pharmacophores containing methoxy groups, highlighting the properties in different biological models, including colorectal cancer. [31,56] Besides, Alhakamy and colleagues [57] also reported the in vitro anticancer activity of different coumarinchalcone hybrids. They showed two active molecules with methoxy substituents at the 3', 5' positions of the aroyl rings, with IC 50 values in the range of 6.8 μM and 17.2 μM on breast cancer cells (MCF-7 and MDA-MB-231).…”
Section: Effect Of Chalcone-coumarin Hybrids On Cell Viabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 4j caused a signicant increase (P < 0.05) in the cell population of the G0/G1-phase (the non-proliferating cell proportion) from 55.71% to 74.14% compared to the control cells, indicating cell cycle arrest and implying that G0/G1 cell cycle arrest is a fundamental mechanism of the anticancer activities of coumarin derivatives, as previously reported. 50 Reciprocally, treatment with 4j showed a meaningful decrease in the cell percentage of the S phase (the DNA synthesis phase) aer 48 h treatment from 17.62% to 9.86% concomitantly with a decrease in the cell percentage in the G2/M phase from 26.67% to 16.00% (Fig. 3A and B), respectively.…”
Section: Biologymentioning
confidence: 74%
“…Coumarins are secondary metabolites of benzopyrones found in several plant genera. According to various studies, these compounds and their derivatives represent an important source of new treatments, especially as antioxidants, antimicrobials, antineoplastics, and anti-inflammatory agents [ 1 , 2 , 3 , 4 , 5 , 6 ]. Coumarins are the major compounds present in Pterocaulon Ell.…”
Section: Introductionmentioning
confidence: 99%